De novo development of small cyclic peptides that are orally bioavailable - Merz, Manuel L.; Habeshian, Sevan; Li, Bo; David, Jean-Alexandre G. L.; Nielsen, Alexander L.; Ji, Xinjian; Il Khwildy, Khaled; Duany Benitez, Maury M.; Phothirath, Phoukham; Heinis, Christian (Nature chemical biology, 2024)
Cyclic peptides can bind challenging disease targets with high affinity and specificity, offering enormous opportunities for addressing unmet medical needs. However, as with biological drugs, most cyclic peptides cannot be applied orally because they are rapidly digested and/or display low absorption in the gastrointestinal tract, hampering their development as therapeutics. In this study, we developed a combinatorial synthesis and screening approach based on sequential cyclization and one-pot peptide acylation and screening, with the possibility of simultaneously interrogating activity and permeability. In a proof of concept, we synthesized a library of 8,448 cyclic peptides and screened them against the disease target thrombin. Our workflow allowed multiple iterative cycles of library synthesis and yielded cyclic peptides with nanomolar affinities, high stabilities and an oral bioavailability (%F) as high as 18% in rats. This method for generating orally available peptides is general and provides a promising push toward unlocking the full potential of peptides as therapeutics. Cyclic peptides show promise for modulating difficult disease targets; however, they often cannot be administered orally. The authors developed a method to synthesize and screen large libraries of small cyclic peptides while enabling the simultaneous interrogation of activity and permeability. This approach was applied to the disease target thrombin to discover peptides with high affinity, stability and oral bioavailability of up to 18% in rats.